For better or worse? : how political consultants are changing elections in the United States - Dulio, David A. (State University of New York Press, 2004)
"For Better or Worse? offers a fresh look at how professional campaign consultants have both positive and negative effects on democracy in the United States. Questioning much of the previailing conventional wisdom, David A. Dulio employs a unique set of data that empirically examines consultants' own attitudes and beliefs to evaluate where they stand in modern democratic elections. Furthermore, he explores their relationships with candidates, voters, political parties, and the media, revealing that political consultants play an integral role in U.S. elections.